1990
DOI: 10.1515/hfsg.1990.44.6.439
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Degradation of Wood Treated with Fire Retardants. II. Strength Losses

Abstract: The correlation between strength loss of wood due to thermal degradation and the progress of the first peak reaction observed in DSC measurements was studied.Test materials were untreated sugar pine and sugar pine treated with the fire retardant Chemicals zinc Chloride and boric acid. Toughness and MOR losses were found to be linearly related to the fractional conversion, which can be calculated from the kinetic parameters determined by DSC. By assuming that the total strength loss due to fire retardant treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In addition, wood treated with acid (Kass et al 1970) showed a convincing correlation between MOR and pentosan content. This idea was pursued further (Berndt et al 1990), and the authors attempted to correlate the area of this exothermic peak with the strength loss of FR-treated wood. Under this proposed theory, some loadsharing capacity would not only be due to covalent or secondary chemical bonding, but to mechanical entanglements between hemicellular sidechains and zones of amorphous cellulose or other matrix components.…”
Section: Microfibril Compared With Matrix Failurementioning
confidence: 99%
“…In addition, wood treated with acid (Kass et al 1970) showed a convincing correlation between MOR and pentosan content. This idea was pursued further (Berndt et al 1990), and the authors attempted to correlate the area of this exothermic peak with the strength loss of FR-treated wood. Under this proposed theory, some loadsharing capacity would not only be due to covalent or secondary chemical bonding, but to mechanical entanglements between hemicellular sidechains and zones of amorphous cellulose or other matrix components.…”
Section: Microfibril Compared With Matrix Failurementioning
confidence: 99%
“…It is well known that some guanidine compounds are one of most effective and economical flame-retardants for hemp. Some authors suggested that these compounds could improve flame retardance of hemp and accelerate the formation of a carbonized layer on the materials [2,3]. It was reported that such additives could lead to a lowering of the decomposition temperature and a higher char yield [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that some guanidine compounds are one of most effective and economical flame-retardants for wood. Some authors suggested that these compounds could improve flame retardance of wood and accelerate the formation of a carbonized layer on the materials [2,3]. It was reported that such additives could lead to a lowering of the decomposition temperature and a higher char yield [4].…”
Section: Introductionmentioning
confidence: 99%